2016
DOI: 10.1007/s11255-016-1350-8
|View full text |Cite
|
Sign up to set email alerts
|

Prostate health index (PHI) and prostate-specific antigen (PSA) predictive models for prostate cancer in the Chinese population and the role of digital rectal examination-estimated prostate volume

Abstract: PHI had better performance over PSA-based models and could reduce unnecessary biopsies. A DRE-assessed PV can replace TRUS-assessed PV in multivariate prediction models to facilitate clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 19 publications
1
30
0
1
Order By: Relevance
“…They could help to distinguish PCa from benign prostate tissue, and there was also a tendency to discriminate aggressive (GS 7) from potentially indolent forms of PCa. The AUC of %p2PSA and PHI were similar to other Asian series [20–23].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…They could help to distinguish PCa from benign prostate tissue, and there was also a tendency to discriminate aggressive (GS 7) from potentially indolent forms of PCa. The AUC of %p2PSA and PHI were similar to other Asian series [20–23].…”
Section: Discussionsupporting
confidence: 83%
“…In a prospective study of 569 men with PSA levels of 4–10 ng/mL in Hong Kong, Chiu et al. demonstrated that the PHI had better performance over PSA‐based models [22]. In addition, combining the PHI, prostate volume, and age could avoid 38.4% and 55.4% of biopsies at 10% and 20% thresholds of missing PCa, respectively [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17] More importantly, while PCA3 was more accurate at predicting PCa overall, PHI was the most accurate predictor of significant PCa when compared with PCA3, tPSA, or PSAD, and correlated well with the Gleason Score [16,18,19]. This was true in both European and Chinese populations [18,20]. The addition of age, DRE and/or prostate volume (PV) to the PHI did not increase its predictive power in identifying high-grade PCa in Chinese men.…”
Section: Prostate Health Index (Phi)mentioning
confidence: 88%
“…good at correctly identifying those without the disease. The SelectMDx test, for example, had the highest sensitivity (0.957, but speci city 0.336)(21,24,33) and PHI had the highest speci city (0.974, but sensitivity 0.129)(18,40). The MRI-targeted biopsy methods generally had a better balance of sensitivity and speci city, ranging from a sensitivity of 0.965 (speci city 0.597) for MRI using a Prostate Imaging-Reporting and Data System (PI-RADS) threshold ≥ 3(22,41) to 0.770 (speci city 0.68) using fusion biopsy…”
mentioning
confidence: 99%